2020
DOI: 10.3389/fchem.2020.00684
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructures Formed by Custom-Made Peptides Based on Amyloid Peptide Sequences and Their Inhibition by 2-Hydroxynaphthoquinone

Abstract: Extensive research on amyloid fibril formations shows that certain core sequences within Aβ peptide play an important role in their formation. It is impossible to track these events in vivo. Many proteins and peptides with such core sequences form amyloid fibrils and such Aβ sheet mimics have become excellent tools to study amyloid fibril formation and develop therapeutic strategies. A group of peptides based on amyloid peptide sequences obtained from PDB searches, where glycine residues are substituted with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 59 publications
(99 reference statements)
0
5
0
Order By: Relevance
“…The peptide, EKKE was investigated at three different pH values, 3.6, 7.4, and 11.7 for its ability to self‐assemble into higher‐order β‐sheet fibrils/amyloid nanostructures by following the routinely used assay for the formation of β‐sheet self‐assembly into amyloid nanostructures 24–26 . The amyloid‐specific fluorescent dye, ThT, on its own shows a maximum fluorescence emission at 450 nm, and when bound to fibrils redshifts to about 490 nm together with enhanced intensity 27 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The peptide, EKKE was investigated at three different pH values, 3.6, 7.4, and 11.7 for its ability to self‐assemble into higher‐order β‐sheet fibrils/amyloid nanostructures by following the routinely used assay for the formation of β‐sheet self‐assembly into amyloid nanostructures 24–26 . The amyloid‐specific fluorescent dye, ThT, on its own shows a maximum fluorescence emission at 450 nm, and when bound to fibrils redshifts to about 490 nm together with enhanced intensity 27 .…”
Section: Resultsmentioning
confidence: 99%
“…The peptide, EKKE was investigated at three different pH values, 3.6, 7.4, and 11.7 for its ability to self-assemble into higher-order β-sheet fibrils/amyloid nanostructures by following the routinely used assay for the formation of β-sheet self-assembly into amyloid nanostructures. [24][25][26] The amyloid-specific fluorescent dye, ThT, on its own shows a maximum fluorescence emission at 450 nm, and when bound to fibrils redshifts to about 490 nm together with enhanced intensity. 27 The change in the fluorescence emission when followed after its addition to the peptide dissolved in an aqueous buffer shows a steady increase in intensity (Figure 1A,D,G) at different pH conditions implying the binding of ThT to β-sheet structures formed by the peptide.…”
Section: Amyloid Forming Propensity Of the Designed Hydrophilic Pepti...mentioning
confidence: 99%
“…Studies have shown that peptide samples in the solid state can have granular, spherical morphologies and a filamentous structure [39,40]. The structure of the peptide may affect the induced deposition [41].…”
Section: Discussionmentioning
confidence: 99%
“…All the aforementioned experiments showed that active peptides could mineralize dentin collagen fibril surfaces and interstitial areas of microfibrils. However, according to the literature, the active peptide structure may affect the morphology of the generated and deposited HA crystals (Mannem et al, 2020). In the experiments conducted by Xiu Peng's group, the deposits formed after remineralization of active and inactive peptides showed two different crystalline forms, namely flakes and needles (Peng et al, 2021).…”
Section: Active Peptidesmentioning
confidence: 99%